Painting Borges : philosophy interpreting art interpreting literature - Gracia, Jorge J. E. (State University of New York Press, 2012)
"A provocative examination of the artistic interpretation of twelve of Borges' most famous stories. In Painting Borges, Jorge J.E. Gracia explores in depth the artistic interpretation of fiction using a novel and philosophically sophisticated approach. The book presents a provocative theory of the artistic interpretation of literature, thus contributing both to aesthetics and hermeneutics; it provides original artistic and philosophical interpretations of twelve of Borges's most famous stories, thus making new inroads in to the understanding of Borges's work; and it introduces readers to recent figurative Argentinean and Cuban art, two of the most vibrant artistic currents today. The book breaks new ground because, although the artistic interpretation of literature is nothing new in the history of art, the philosophical exploration of how artists have interpreted literature is a topic that has been largely ignored."--Project Muse
Keywords: Borges, Jorge Luis, -- 1899-1986 -- Themes, motives.; Borges, Jorge Luis, -- 1899-1986 -- Illustrations.; Borges, Jorge Luis, -- 1899-1986; Art and literature.; Art -- Philosophy.; Art et littérature.; Art -- Philosophie.; ART -- Performance.; ART -- Reference.; Art and literature; Art -- Philosophy; Themes, motives; Illustrated works